Implementation of the Kanban Method to a crm Software based in the Open Source Platform Vtiger - Botia Mendivelso, María Fernanda; Súarez Valderrama, María Teresa; Romero Villalobos, Oswaldo Alberto (Ingeniería Solidaria, 2016)
Introduction: This article is the result of the research “Importance of the CRM Software simplicity from the user’s perspective”, conducted by the Research Group in Interoperability in Academic Networks (GIIRA) of the District University Francisco Jose de Caldas, during the year 2015.Methodology: The Kanban method was implemented in the Open Source Vtiger-based platform, and 20 user companies were monitored for data collection in order to compare their usage with the information obtained during the first semester of 2015. During that period, the platform had an interface similar to Vtiger’s. Results: 85 % of the companies increased their use of the platform significantly up to 310 %. The other 10 % did not present significant variations, and the remaining 5 % registered a decrease in their use of the platform.Discussion: The implementation of the Kanban method in the Customer Relationship Management (CRM) software allows access to commercial management information in an organized manner, thus highlighting key facts that are easily conclusive, and redirecting additional information, if necessary.